The association between network literacy and subjective well-being among middle-aged and older adults - Sun, Lin; Xiong, Juan; Zhang, Chong (Frontiers in Psychology, 2025)
IntroductionWith the advent of the digital age, network literacy has become a pivotal indicator for assessing the social adaptability and quality of life among middle-aged and older adults.MethodsThis study is based on data from the Chinese Family Panel Studies (CFPS), utilizing three waves of data from 2014, 2018, and 2020. We employ a fixed-effects panel regression and Bootstrap method to explore the association between network literacy and subjective well-being of this demographic and its mediating mechanisms.ResultsThe research findings indicate a significant positive correlation between network literacy and subjective well-being among middle-aged and older adults, with both network usage literacy and network perception literacy positively promoting their subjective well-being. Interpersonal relationships play a positive mediating role between network literacy and subjective well-being. Furthermore, the frequency of online social interaction and entertainment in network usage literacy, as well as the importance of these activities in network perception literacy, have significant positive relationships with subjective well-being.ConclusionThese findings underscore the importance of enhancing network literacy among middle-aged and older adults, providing a foundation for policymakers and community organizations to facilitate their integration into the digital society. This integration can enable them to enjoy the Internet's convenience and entertainment, thereby improving their quality of life and well-being. Future research should extend its focus to the multidimensional aspects of network literacy and its enduring effects on the well-being.